Pancreatic Cancer Cachexia: The Role of Nutritional Interventions - Mitchell, Toni (Healthcare (Basel), 2019)
Pancreatic cancer is a cancer with one of the highest mortality rates and many pancreatic cancer patients present with cachexia at diagnosis. The definition of cancer cachexia is not consistently applied in the clinic or across studies. In general, it is “defined as a multifactorial syndrome characterised by an ongoing loss of skeletal muscle mass with or without loss of fat mass that cannot be fully reversed by conventional nutritional support and leads to progressive functional impairment.” Many regard cancer cachexia as being resistant to dietary interventions. Cachexia is associated with a negative impact on survival and quality of life. In this article, we outline some of the mechanisms of pancreatic cancer cachexia and discuss nutritional interventions to support the management of pancreatic cancer cachexia. Cachexia is driven by a combination of reduced appetite leading to reduced calorie intake, increased metabolism, and systemic inflammation driven by a combination of host cytokines and tumour derived factors. The ketogenic diet showed promising results, but these are yet to be confirmed in human clinical trials over the long-term. L-carnitine supplementation showed improved quality of life and an increase in lean body mass. As a first step towards preventing and managing pancreatic cancer cachexia, nutritional support should be provided through counselling and the provision of oral nutritional supplements to prevent and minimise loss of lean body mass.